2009
DOI: 10.1021/tx900281u
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 23 Polycyclic Aromatic Hydrocarbons in Smokeless Tobacco by Gas Chromatography−Mass Spectrometry

Abstract: Smokeless tobacco contains 28 known carcinogens and causes precancerous oral lesions and oral and pancreatic cancer. A recent study conducted by our research team identified 8 different polycyclic aromatic hydrocarbons (PAH) in U.S. moist snuff, encouraging further investigations of this group of toxicants and carcinogens in smokeless tobacco products. In this study, we developed a gas chromatography-mass spectrometry method that allows simultaneous analysis of 23 various PAH in smokeless tobacco after a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 26 publications
3
61
2
Order By: Relevance
“…The development of products with lower nitrosamine (Osterdahl, Jansson & Paccou, 2004) and polycyclic aromatic hydrocarbon (PAH) levels (Stepanov et al, 2010) also means that the factual risks are likely to be lower today than with the snus types used 20-30 years ago (Lee & Hamling, 2009). A group of EU-appointed experts performed a review of studies of the risk of harm to health from combustible and non-combustible tobacco, and concluded that snus was 70-90 per cent less harmful to users' health than smoking (The Scientific Committee on Emerging and Newly-Identified Health Risks (SCENIHR), 2008).…”
Section: Perceptions Of Relative Risk Of Disease and Addiction From Cmentioning
confidence: 99%
“…The development of products with lower nitrosamine (Osterdahl, Jansson & Paccou, 2004) and polycyclic aromatic hydrocarbon (PAH) levels (Stepanov et al, 2010) also means that the factual risks are likely to be lower today than with the snus types used 20-30 years ago (Lee & Hamling, 2009). A group of EU-appointed experts performed a review of studies of the risk of harm to health from combustible and non-combustible tobacco, and concluded that snus was 70-90 per cent less harmful to users' health than smoking (The Scientific Committee on Emerging and Newly-Identified Health Risks (SCENIHR), 2008).…”
Section: Perceptions Of Relative Risk Of Disease and Addiction From Cmentioning
confidence: 99%
“…Even though snus is not a new product in the Norwegian market, the present type of snus is different from previous types. Because of the production and storage methods, the new Swedish snus has a lower level of tobacco specific nitrosamines and polycyclic aromatic hydrocarbon compared with other smokeless tobacco products, including those used in Scandinavia before 1990 (Borgerding, Bodnar, Curtin, & Swauger, 2012;Stepanov et al, 2009). …”
Section: Health Consequencesmentioning
confidence: 99%
“…PAHs are present in some unburned tobacco products, particularly those containing fire-cured tobacco varieties. 67 During fire curing, PAHs in combustion fumes generated by smoldering wood are deposited on the tobacco leaves. 8 …”
Section: Introductionmentioning
confidence: 99%